Acute Pancreatitis Secondary to Hypertriglyceridemia during Pregnancy - Alenezi, Raed; Almutairi, Waleed M.; Saleh, Najla; Aldahash, Raed; Al-Saleh, Yousef (Journal of Diabetes and Endocrine Practice, 2022)
Introduction Hypertriglyceridemia (HTG) (triglycerides > 1,000 mg/dL [11.3 mmol/L]) has been associated with a high risk of developing acute pancreatitis (AP) in pregnant women, but this condition is rare. We present the case of a pregnant Saudi with AP secondary to HTG.Case Report A 27-year-old Saudi female presented at 30 weeks' gestational age with abdominal pain, nausea, and vomiting of 4 days' duration. AP was diagnosed based on clinical presentation, high lipase, and abdominal ultrasound findings. Her triglyceride level was 58 mmol/L. Fenofibrate and intravenous regular insulin infusion with dextrose were started, which decreased triglycerides by the third day from 58.8 to 29 mmol/L (50% reduction) with a further reduction to 11 mmol/L (81%) by day 7 of her admission. Labor was induced at 37 weeks of gestation, and she delivered a healthy neonate.Conclusion We report successful treatment of AP in pregnancy with intravenous insulin and fenofibrate. Several case reports have discussed the therapeutic option of AP induced by HTG in pregnancy. Lipid-lowering agents are category C in pregnancy. However, few case reports indicate their safety. Insulin, heparin, and apheresis have also been used during pregnancy without any complications.
Keywords: acute pancreatitis; hypertriglyceridemia; pregnancy